The Survey on the Implementation of Online Tutoring Information Services at SMP PGRI 1 Buduran Sidoarjo - Anita Arofah Halimah Yasmin; Aniek Wirastania (Universitas PGRI Adi Buana Surabaya, 2021)
This study aims to determine tutoring services to identify the implementation of information services for students of SMP PGRI 1 Buduran during the pandemic. The method applied was descriptive qualitative, in the form of a survey research involving BK SMP PGRI 1 Buduran Sidoarjo teachers as informants. The data collection technique used in this study used data triangulation carried out by interview and observation methods, as well as document data collection. The conclusion from the results shows that the tutoring information service shows that the implementation of tutoring services during this pandemic is not effective enough due to limited time, place, and the situation is quite difficult to meet face to face with students directly, but counselors always try to provide good services. and continuously according to student needs so that students even during the pandemic can still get proper and good learning.